The effectiveness of PAIKEM strategy in the curriculum of KTSP and 2013 for grade 4 students - Hidayati, Peni Nur (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2018)
This research aimed to understand the effectiveness of PAIKEM (Active, Innovative, Creative, Effective, and Enjoyable Learning) strategy in the KTSP (School Based Curriculum) in Madrasah Ibtidaiyah (MI) Ma’arif Gedangan and in the Curriculum of 2013 in MI Ma’arif Mangunsari applied in the 4th Grade students in the academic year of 2016/2017.  The curriculum changing gave an impact in education especially on the use of learning strategy for teachers to reach the education goal.  This research was descriptive qualitative research which used observation, interview, and documentation as the method to collect the data. It used field research as the research method which was conducted by researcher collaborated with teachers. The research result showed that the use of PAIKEM strategy is more effective when it was used in the curriculum of 2013 than applied in KTSP curriculum. The implementation of PAIKEM strategy in the KTSP curriculum is less effective applied in the classroom. It was proven with the students’ interaction in the class. Many students were less active during the learning activities. However, teacher and students as the object of the research could follow the activities which applied PAIKEM strategy in the classroom. From the research result, it can be concluded that PAIKEM strategy can be implemented in KTSP and the curriculum of 2013. The implementation of PAIKEM strategy in the curriculum of 2013 is more effective than in the KTSP curriculum.